The Promiscuous Life of Plant NUCLEAR FACTOR Y Transcription Factors([W]) - Petroni, Katia (American Society of Plant Biologists, 2012)
The CCAAT box is one of the most common cis-elements present in eukaryotic promoters and is bound by the transcription factor NUCLEAR FACTOR Y (NF-Y). NF-Y is composed of three subunits, NF-YA, NF-YB, and NF-YC. Unlike animals and fungi, plants have significantly expanded the number of genes encoding NF-Y subunits. We provide a comprehensive classification of NF-Y genes, with a separation of closely related, but distinct, histone fold domain proteins. We additionally review recent experiments that have placed NF-Y at the center of many developmental stress-responsive processes in the plant lineage.